Pengelolaan Pembelajaran Matematika Berbasis Al Qur’an di Sekolah Menengah Pertama - Saksono, Deky Yudha; Sutama, Sutama (Jurnal VARIDIKA, 2015)
This study aims to describe the mathematicsbased learning management Qur?an conducted in Junior High School Kendal district, Central Java. This study uses the approach of research and development. Data collection techniques, observation, interviews, and documentation. Validity of data with triangulation techniques and triangulation of sources. Results of the study: (1) The management of learning that has been done is still using school math learning in general, (2) Management based math learning the Qur?an through the stages of the addition of paragraph choices on the subject matter has not been made, (3) based learning management Qur ?an has not been effective so no link between mathematics and the Qur?an.